EXPLORATION OF STUDENT’S MATHEMATICAL CONNECTION ABILITY BASED ON LEARNING MOTIVATION - Meiliati, Rafika; Salido, Achmad; aswin, aswin; Husain, Dayana Sabila (JME (Journal of Mathematics Education), 2025)
This study aimed to explore and explain students’ mathematical connection abilities based on their levels of learning motivation. A qualitative investigative approach involved junior high school students categorized into three motivation levels: high, moderate, and low. Data were collected through a learning motivation questionnaire and problem-solving tasks to assess students’ mathematical connection skills. The results revealed that highly motivated students demonstrated the strongest abilities, characterized by their capacity to connect various mathematical concepts, effectively use visual representations, and apply concepts in real-life and interdisciplinary contexts. In contrast, moderately motivated students tended to rely on basic procedures without developing a comprehensive conceptual understanding, while students with low motivation struggled to comprehend and relate concepts, often copying information without formulating appropriate solution strategies. These findings highlight the critical role of learning motivation in fostering mathematical connection skills. Therefore, implementing instructional strategies that enhance student motivation—such as problem-based and contextual learning approaches—is essential for promoting more profound understanding and stronger mathematical connections.